2015
DOI: 10.4236/fns.2015.614138
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin-Resistant <i>Staphylococcus aureus</i> in Raw Hamburgers and Ready-to-Eat Sandwiches Commercialized in Supermarkets and Fast Food Outlets in Brazil

Abstract: Although well known, Staphylococcus aureus is a bacterium that remains widely studied because of its high pathogenic potential and its ability to develop resistance to antibiotics routinely used in clinical practice. The present study investigated the occurrence of methicillin-resistant Staphylococcus aureus (MRSA) in hamburgers and sandwiches sold in supermarkets and fast food outlets in Salvador, BA, Brazil. Fifty samples of frozen raw hamburgers (25: beef and 25: chicken) and 50 samples of ready-to-eat sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…However, Kumar et al [28] also reported that 3 (15.78%) were S. aureus which was significantly lower than our finding of 30 (60%). Contreras et al [29] also revealed that MRSA was detected in 32% of the hamburgers and 8% of the sandwiches investigated in Brazil, which was within the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
“…However, Kumar et al [28] also reported that 3 (15.78%) were S. aureus which was significantly lower than our finding of 30 (60%). Contreras et al [29] also revealed that MRSA was detected in 32% of the hamburgers and 8% of the sandwiches investigated in Brazil, which was within the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Food products surveyed as meat and its products are widely known to be an important reservoir and main source of MRSA in humans [8]. Therefore, the present study was conducted to investigate the incidence of coagulase-positive S. aureus and methicillin-resistant S. aureus (MRSA) strains in different popular ready-to-eat meat sandwiches (kofta, burger, shawerma, and luncheon) in Benha city.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the isolates harbored the concurrent presence of two antibiotic resistance genes, particularly aacA-D + blaZ , tetK + blaZ , aacA-D + tetK , aacA-D + gyrA, and ermA + blaZ together. A high prevalence of multi-drug resistant S. aureus was reported in previous investigations as well [ 44 – 46 ]. However, the literature review showed no report on the prevalence of gyrA , vatC , blaZ , vatA , cat1 , rpoB , dfrA , linA , vatB , msrA , aacA-D , ermA , grlA , tetK, and tetM genes among the S. aureus bacteria recovered from ready-to-eat food samples.…”
Section: Discussionmentioning
confidence: 58%